Pitfalls in scoring MR images of rheumatoid arthritis wrist and metacarpophalangeal joints. (12th January 2005) - McQueen, F; Østergaard, M; Peterfy, C; Lassere, M; Ejbjerg, B; Bird, P; O'Connor, P; Genant, H; Shnier, R; Emery, P; Edmonds, J; Conaghan, P
Abstract : This paper outlines the most important pitfalls which are likely to be encountered in the assessment of magnetic resonance images of the wrist and metacarpophalangeal joints in patients with rheumatoid arthritis. Imaging artefacts and how these can be recognised using various sequences and views are discussed. Normal structures such as interosseous ligaments and nutrient foramina may appear prominent on certain images and need to be identified correctly. Pathological change in the rheumatoid hand involves many tissues and when substantial damage has occurred, it may be difficult to identify individual structures correctly. Bone erosion, bone oedema, synovitis, and tenosynovitis frequently occur together and in close proximity to each other, potentially leading to false positive scoring of any of these. Examples are given to illustrate the various dilemmas the user of this atlas may face when scoring the rheumatoid hand and suggestions are made to assist correct interpretation of what can be very complex images.